2003
DOI: 10.1303/aez.2003.241
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of trehalose in aphid hemolymph

Abstract: The major components of hemolymph were examined by 1 H-NMR in seven species of aphids, Acyrthosiphon pisum, Aphis gossypii, Aphis sambuci, Lachnus tropicalis, Megoura crassicauda, Myzus persicae and Uroleucon nigrotuberculatum. Trehalose was detected as the main component from these aphids, and its concentrations in these insects were much higher (196 mM in L. tropicalis to 926 mM in A. gossypii) than those of two other homopterous insects, Cryptotympana facialis (91 mM) and Nephotettix cincticeps (53 mM). Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 24 publications
1
32
1
Order By: Relevance
“…In a previous paper, we indicated that trehalose is a major component in the hemolymph of homopterous insects; aphid, leafhopper and cicada (Moriwaki et al, 2003). Trehalose synthesized in rice planthoppers may also be utilized as an energy source like in most insects.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous paper, we indicated that trehalose is a major component in the hemolymph of homopterous insects; aphid, leafhopper and cicada (Moriwaki et al, 2003). Trehalose synthesized in rice planthoppers may also be utilized as an energy source like in most insects.…”
Section: Resultsmentioning
confidence: 99%
“…The forelegs of rice planthoppers were pulled out with forceps and the exuding hemolymph collected with a 1 ml microcapillary tube (EM minicaps, Hirschmann ® laborgerate). Hemolymph obtained was immediately diluted with 500 ml heavy water (D 2 O) containing 0.1 ppm validoxylamine A (VAA) and with a small amount of phenylthiourea as previously described (Moriwaki et al, 2003). A total of 2-10 ml of hemolymph was collected from 20 to 100 individuals of each species.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations